On the reversibility of dislocation slip during small scale low cycle fatigue. (1st August 2015) - Kirchlechner, C.; Imrich, P.J.; Liegl, W.; Pörnbacher, J.; Micha, J.-S.; Ulrich, O.; Motz, C.
Abstract: The evolution of low cycle fatigue damage in copper is studied by in situ micro Laue diffraction. Free standing single crystalline micro-cantilevers with a cross-section of 10 × 10 μm 2 were loaded in displacement controlled mode with a surface strain amplitude up to 5%. The point to point misorientation and the diffraction peak width as a measure of geometrically necessary dislocation density was analyzed locally during deformation and globally after 0, 1/4, 1/2, 3/4, 1 and multiples up to a maximum of 22 full cycles. Two different behaviors were observed (i) samples geometrically suppressing cross-slip show a steady state deformation pattern with dislocations in a pile-up. (ii) The sample with cross-slip does not reach a steady state with dislocations accumulating at the neutral plane.